miR-144-3p Promotes Adipogenesis Through Releasing C/EBPα From Klf3 and CtBP2 - Shen, Linyuan; Li, Qiang; Wang, Jinyong; Zhao, Ye; Niu, Lili; Bai, Lin; Shuai, Surong; Li, Xuewei; Zhang, Shunhua; Zhu, Li (Frontiers in Genetics, 2018)
MicroRNAs (miRNAs), a class of small non-coding RNAs that have been proved as novel and potent regulators of adipogenesis. A previous study found out that miR-144 was a biomarker of type 2 diabetes, but the role of miR-144 in regulating adipogenesis is still unclear. In the present study, the expression of miR-144 increased both in obese mice and during the 3T3-L1 differentiation process. Overexpression of miR-144 suppressed the expression of cell cycle regulatory factors and inhibited preadipocytes proliferation. Besides, overexpression of miR-144 accelerated lipid accumulation in adipocytes and positively regulated its adipogenesis, which also accompanied by increasing the expression of genes related to fatty acid synthesis and decreasing the expression of genes involved in fatty acid oxidation. Furthermore, luciferase activity assays indicated miR-144 directly targeted Klf3 and CtBP2. The process also was confirmed by the mRNA and protein expression of Klf3 and CtBP2 that were suppressed by miR-144. Furthermore, miR-144 targeting Klf3/CtBP2 would induce C/EBPα activity by releasing corepressors (Klf3 and CtBP2) from its promoter region. Moreover, we also observed miR-144 could promote adipogenesis in mice injected with miR-144 agomir through tail-vein injection. Taken together, these results support that miR-144 can facilitate adipogenesis both in vitro and in vivo, which implies that miR-144 could be a target for therapeutic intervention in obesity and metabolic syndrome in the future